Analisis U-Turn (Putaran Balik) Terhadap Kelancaran Arus Lalu Lintas : Studi Kasus Jalan Trikora Manokwari - Jimmy Harrison Nababan; Semuel Rorrong; David David (Jurnal Sipil Terapan, 2025)
U-Turn Facilities serve to accommodate vehicles changing the direction of travel. Trikora road Manokwari has a U-Turn that causes traffic flow conflicts. The problem occurs because the vehicle cannot make a U-Turn movement properly, so it takes more time when making a U-Turn movement. The purpose of study was to analyze traffic flow conflicts, road geometrics, and level of service. Data collection method by direct observation for 7 days at 07.00 AM to 08.00 AM, 08.00 AM to 09.00 AM, 11.00 AM to 12.00 PM, 12.00 PM to 13.00 PM, 16.00 PM to 17.00 PM and 17.00 PM to 18.00 PM at the research location. Data analysis using MKJI 1997. The results of data analysis obtained a maximum traffic volume of 1308 pcu/hour. Side obstacle class Medium with a weighted frequency 390 with industrial area conditions, several shops on the side of the road. Road capacity of 5562 pcu/hour. Maximum vehicle of 24,70 meters. Disturbed traffic flow speed of 27,32 kilometers/hour. Road shoulder width of 1,5 meters. Level of service value of 0,44 (A). Keywords: U-Turn, Road Geometrics, Traffic Flow, Capacity